LEGAL PROTECTION OF CHILDREN AS VICTIMS OF CRIMES OF SEXUAL VIOLENCE IN THE LEGAL AREA OF THE RESORT POLICE OF EAST LUWU DISTRICT - Asrul .; Hambali Thalib; Hasan Kadir (P3M Stia Al Gazali Barru and Meraja media, 2020)
[Full Paper] to pdf Copyright (c) 2020 Meraja journal